Applying Best Practices for Improving the Performance of Software Project Manager - Samih Karim Buo-Oga (المجلة الدولية للحاسبات والمعلوماتية, 2025)
This paper focuses on proposing a quality assurance model for Software Projects Management. This paper presents some important concepts related to this field. It presents the phases and activities of software project management. This paper presents a set of proposed steps for achieving each activity of planning ISs projects. Depending on the proposed steps and a combination of statistical techniques, this paper introduces a proposed quality assurance model for software project management activities. This proposed model can be used to build an automated software tool.